Rapid detection of inter-clade recombination in SARS-CoV-2 with Bolotie. Issue 3 (10th June 2021) - Varabyou, Ales; Pockrandt, Christopher; Salzberg, Steven L; Pertea, Mihaela
Abstract : Varabyou, Pockrandt et al . analyze over 300K SARS-CoV-2 genomes for signs of recombination. Using a novel method to search for recombinant signatures in large datasets of highly similar genomes, they identify 775 high-likelihood recombinant SARS-CoV-2 genomes, including several sub-lineages persisting in the population. Their results indicate the need to take recombinant genomes into account when performing phylogenetic analysis since anomalies can have adverse effects on the topologies of inferred trees. Abstract: The ability to detect recombination in pathogen genomes is crucial to the accuracy of phylogenetic analysis and consequently to forecasting the spread of infectious diseases and to developing therapeutics and public health policies. However, in case of the SARS-CoV-2, the low divergence of near-identical genomes sequenced over a short period of time makes conventional analysis infeasible. Using a novel method, we identified 225 anomalous SARS-CoV-2 genomes of likely recombinant origins out of the first 87, 695 genomes to be released, several of which have persisted in the population. Bolotie is specifically designed to perform a rapid search for inter-clade recombination events over extremely large datasets, facilitating analysis of novel isolates in seconds. In cases where raw sequencing data were available, we were able to rule out the possibility that these samples represented co-infections by analyzing the underlying sequence reads. The Bolotie software and other data from our study are available at https://github.com/salzberg-lab/bolotie .